Government size, country size, openness and economic growth in selected MENA countries - Mahmoud M. Sabra (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The purpose of this article is to examine the interconnected relationships between government size, country size, openness and economic growth. In fact, more trade openness increases government size, which lays stabilizer role against external shocks and GDP volatility. More country size leads to lower government share to GDP from one side and less openness from other side, where as per capita expenditure on public goods is lower, and large markets enjoy more productivity and less incentives for large market to increase openness than the small markets. Finally, economic growth and government have a negative relationship if government size exceeds the optimal size. Design/methodology/approach - We employ three models, which two of them are using 2SLS technique and the third model is using GMM system analysis to examine these relationships in eight selected MENA countries. Our panel data is for the period from 1977-2013 sourced from the World Development Indicators of the World Bank. Findings - Results prove literature proposed hypotheses for the selected region and period, and show that government share to GDP exceeds the optimal size. Moreover, more growth can be realized through more integration in the world economy. Research limitations/implications - Data limitation led to the inclusion of only eight countries of MENA region. We recommend to convert government expenditure to investment and infrastructure instead of social transfer and current expenditure. Furthermore, more studies could be done about the government expenditure structure. In addition, we recommend to minimize government intervention to the market. Finally, growth of government does not improve investment environment or reduce transactions costs, and it crowds out private sector. Originality/value - This is the first work in MENA region, and using recent econometric techniques in subject according to our knowledge.
Keywords: H10; F43; C33; 330; openness; country size; government size; economic growth and system GMM panel data